Effect of Operator's Experience on Proficiency in Mechanical Thrombectomy: A Multicenter Study. Issue 9 (8th July 2021) - Zhu, François; Ben Hassen, Wagih; Bricout, Nicolas; Kerleroux, Basile; Janot, Kevin; Gory, Benjamin; Anxionnat, René; Richard, Sébastien; Marchal, Adrien; Blanc, Raphael; Piotin, Michel; Consoli, Arturo; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We aimed to evaluate among trained interventional neuroradiologist, whether increasing individual experience was associated with an improvement in mechanical thrombectomy (MT) procedural performance metrics. Methods: Individual MT procedural data from 5 centers of the Endovascular Treatment in Ischemic Stroke registry and 2 additional high-volume stroke centers were pooled. Operator experience was defined for each operator as a continuous variable, cumulating the number of MT procedures performed since January 2015, as MT became standard of care or, if later than this date, since the operator started performing mechanical thrombectomies in autonomy. We tested the associations between operator's experience and procedural metrics. Results: A total of 4516 procedures were included, performed by 36 operators at 7 distinct centers, with a median of 97.5 endovascular treatment procedures per operator (interquartile range, 57–170.2) over the study period. Higher operator's experience, analyzed as a continuous variable, was associated with a significantly shorter procedural duration (β estimate, −3.98 [95% CI, −5.1 to −2.8]; P <0.001), along with local anesthesia and M1 occlusion location in multivariable models. Increasing experience was associated with better Thrombolysis in Cerebral Infarction scores (estimate, 1.02 [1–1.04]; P =0.013). Conclusions: In trained interventional neuroradiologists, increasing experience in MT is associated with significantly shorter procedural duration and better reperfusion rates, with a theoretical ceiling effect observed after around 100 procedures. These results may inform future training and practice guidelines to set minimal experience standards before autonomization, and to set-up operators' recertification processes tailored to individual case volume and prior experience.